The emission structure and kinematics of hot molecular gas and ionized gas in galaxy NGC 6814 - Baierle, Pedro Albino; Riffel, Rogemar Andre (Cadernos de Astronomia, 2023)
We use integral field spectroscopy observations of the inner 260×260 pc2 of galaxy NGC 6814 to map the emission structure and kinematics of hot molecular gas and ionized gas at a spatial resolution of ∼ 20 pc. The observations were carried out with the Near-Infrared Field Spectrograph (NIFS) instrument installed on the Gemini North Telescope. The ionized gas emission is studied via the hydrogen recombination emission line Brγ, while the hot molecular gas is traced by the H2 2.1218 μm emission line. From the fitting of the emission- line profiles by Gaussian functions, we constructed two-dimensional maps for the flux, velocity and velocity dispersion for each emission line. While H2 presents emission over the entire field of view, the Brγ emission is restricted to radii smaller than 50 pc from the nucleus. The gas motions in both phases are consistent with a rotating disk pattern. The o MH2 ≈ 109 M⊙bserved H2 emission is likely associated to heating of the gas by X-rays from the active nucleus and the mass of hot molecular gas is estimated as MH2 ≈ 109 M⊙. The mass of ionized gas is MH II ≈ 4.4 × 104 M⊙. An increase in the velocity dispersion is observed in the nucleus, which we attribute to motions of gas subjet to the gravitational potential of the central supermassive black hole, whose mass is estimated to be MSMBH ≈ 4, 4 × 107 M⊙, consistent with estimates available in the literature.